The Relationship Between Extratropical Cyclone Strength and Atmospheric River Intensity and Position - Zhenhai Zhang; F. Martin Ralph; Minghua Zheng (Geophysical Research Letters)
Abstract Extratropical cyclones (ECs) and atmospheric rivers (ARs) impact precipitation over the U.S. West Coast and other analogous regions globally. This study investigates the relationship between ECs and ARs by exploring the connections between EC strength and AR intensity and position using a new AR intensity scale. While 82% of ARs are associated with an EC, only 45% of ECs have a paired AR and the distance between the AR and EC varies greatly. Roughly 20% of ARs (defined by vertically integrated water vapor transport) occur without a nearby EC. These are usually close to a subtropical/tropical moisture source and include an anticyclone. AR intensity is only moderately proportional to EC strength. Neither the location nor intensity of an AR can be simply determined by an EC. Greater EC intensification occurs with stronger ARs, suggesting that ARs enhance EC deepening by providing more water vapor for latent heat release.